Using self-assessment to extend sustainability competency development - Munro, Tai; King, Martina (My University, 2022)
One of the key benefits of developing sustainability competencies is that they enable students to pursue future work and study opportunities within sustainability despite diverse fields and challenges. However, if students do not also develop their ability to self-assess their own strengths and weaknesses, we risk creating a situation where students are unable to respond to new situations and evolving challenges. Self-assessment is key to enabling individuals to identify current and future needs for education and professional development once they leave the formal education system. Self-assessments are the most often used tool to assess competency development (Redman, Wiek, & Barth, 2021). This is a subject of criticism as opponents argue that students are not skilled in self-assessment. However, Boud and Falchikov (2007) argue that self-assessment is vital to supporting students in becoming life-long learners. Thus, developing self-assessment skills is a necessary complementary competency that we need to support students in developing. In this session, we’ll look at research from a community engaged learning course where students were asked not just to self-assess but to also reflect on how accurate their own self-assessments were and identify areas for future growth and opportunity. Then we’ll discuss and demonstrate how to incorporate similar opportunities to complement key sustainability competency development.
Presented on October 18, October 26 and November 3, 2022, at the Global Conference on Sustainability in Higher Education held online.
Keywords: sustainability competencies; self-assessment; sustainable development goals